ACTIVITY OF MAKASAR FRUIT (Brucea Javanica L. Merr) ON RADICAL ANION SUPEROXIDE IN VIVO - Ari Widiyantoro; Elvi R.P. Wardoyo; Endah Sayekti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
Activity of scavengering radical anion superoxide by extract of Makasar fruit (Brucea javanica L. Merr) have been research with methods of inhibition reduction nitroblue tetrazolium, by in vivo on rat Wistar induction with aflatoxin. Results showed there are inhihition reduction of nitroblue tetrazolium by methanol extract, methanol fraction, ethylacetate fraction, methylen chloride fraction and n-hexane fraction. Phytochemical test showed alkaloid, terpenoid, quinone, polyphenol and steroid.